2017
DOI: 10.1021/acsomega.6b00394
|View full text |Cite
|
Sign up to set email alerts
|

From pH- to Light-Response: Postpolymerization Modification of Polymer Brushes Grafted onto Microporous Polymeric Membranes

Abstract: A microporous pH- and light-responsive membrane that enables remote control over its interfacial properties has been fabricated. pH-Responsiveness was imparted to a porous polypropylene film via grafting of poly(methacrylic acid) brushes from the substrate using argon-plasma-induced free-radical graft polymerization. Morphological changes as a function of grafting level were analyzed using atomic force microscopy. Conversion into a light-responsive membrane was performed via postpolymerization modification to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Though regarded as innately charged, polyelectrolytes frequently contain weakly acidic or basic moieties distributed along the polymer backbone. This can be immensely useful, as monomer groups may protonate or deprotonate depending upon the local environmental conditions, enabling tunable “smart” materials [12,13,14]. Important recent examples include the pH-responsive swelling and collapse of poly(acrylic acid) [PAA] in functionalized nanoporous membranes [15], pH-responsive Saloplastics/Compact polyelectrolyte complexes (COPECs) [16] synthesized using Poly(methacrylic acid) (PMAA) poly(allylamine hydrochloride) (PAH), which find applications in tissue engineering by mimicking mechanical properties of a cartilage [17], self-assembled polyelectrolyte capsules and multilayer thin films for drug delivery purposes [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Though regarded as innately charged, polyelectrolytes frequently contain weakly acidic or basic moieties distributed along the polymer backbone. This can be immensely useful, as monomer groups may protonate or deprotonate depending upon the local environmental conditions, enabling tunable “smart” materials [12,13,14]. Important recent examples include the pH-responsive swelling and collapse of poly(acrylic acid) [PAA] in functionalized nanoporous membranes [15], pH-responsive Saloplastics/Compact polyelectrolyte complexes (COPECs) [16] synthesized using Poly(methacrylic acid) (PMAA) poly(allylamine hydrochloride) (PAH), which find applications in tissue engineering by mimicking mechanical properties of a cartilage [17], self-assembled polyelectrolyte capsules and multilayer thin films for drug delivery purposes [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is the maximum possible value indicating the merge of all B groups to the only cluster and the formation of the bicontinuous structure. The ability to pass rapidly from bicontinuous to lamellae structure could be interesting for practical applications which require a quick change of connectivity, such as molecular switches, elements of electrical circuits, the system for controllable catalysis, and so forth . We believe that such types of reconstruction (lamellaeparking garagelamellae) could be observed in other polymer systems, where self-organization is accompanied by the conformation changes of their constituent parts.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐cleaning membranes possess a thin layer of “smart” materials able to respond to the environment changes, improve membrane surface properties, and mitigate fouling . In this approach, photoresponsive materials can be grafted or coated in order to provide switchable and antifouling properties using light as a noninvasive stimulus …”
Section: Membrane Processesmentioning
confidence: 99%
“…Dübner et al demonstrated a new method for the fabrication of a pH‐ and light‐responsive polypropylene membrane. pH‐responsiveness was imparted via grafting of poly(methacrylic acid) (PMAA) brushes using a plasma‐induced free‐radical graft polymerization.…”
Section: Membrane Processesmentioning
confidence: 99%